Video Animasi sebagai Media untuk Meningkatkan Keterampilan Menggosok Gigi Anak Tunagrahita - Nur’aini Dewi; Fitria Sulistyowati; Widowati Pusporini (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Mentally retarded children have several limitations, one of which is the ability to brush their teeth. This study aims to improve the skills of brushing teeth in sixth grade mentally retarded children at SLB Negeri 1 Sleman. This research is a qualitative descriptive research using classroom action research design. Classroom action research procedures are carried out through a process consisting of 4 stages, namely: 1) planning; 2) implementation; 3) observation; 4) reflection. The method of data collection is by testing, observation and documentation. This classroom action research was conducted in 2 cycles. From the data analysis, it is known that each cycle there is an increase in learning outcomes. The results showed that learning brushing teeth skills with animated video media can improve teeth brushing skills in mentally retarded children. This is indicated by the results of the post-test cycles 1 and 2 which show the results of mastery of the material above the specified criteria, namely 75%.